INNOVATIVE TREATMENT STRATEGIES FOR PATIENTS WITH OVERACTIVE BLADDER AND URGE INCONTINENCE NOT CAUSED BY OBSTRUCTION - Kasimov S. S.; Rahmonberdiyev Kh. K. (Modern American Journals, 2025)
Overactive bladder (OAB) is observed in approximately 25% of patients with various urinary tract disorders, with urge urinary incontinence present in about one-third of these cases. The objective of this study was to enhance treatment outcomes in women with OAB, urge urinary incontinence, and non-obstructive urination by employing a combined pharmacological approach using an α1-adrenergic blocker and an M-anticholinergic agent. Additionally, the study aimed to investigate the correlation between clinical symptoms and urodynamic parameters, as well as assess changes in bladder mucosal microcirculation before and after therapy.